I nomi dei numeri. Considerazioni linguistiche. - MANCO, Alberto (Studii de Ştiintă şi Cultură, 2012)
The learning of more prevalent systems of numbering usually goes on for tens: for a child, counting up to ten is the first and most important moment of sharing a "standard" numeral piece of knowledge. But that same child lives in a world in which eggs and pastries are counted in dozens, time is measured in sixtieths and their submultiples and an indeterminable number of linguistic expressions refer us to numeral universes that are inferior or different to those based on tens. This article will put forward some considerations on what is decidedly a broad and complex issue that transcends the lexical dimension.